The clinical condition rather than cerebrospinal fluid levels may guide the optimal duration of antimicrobial therapy among neonates with bacterial meningitis: A single‐center retrospective study - Ya Hu; Xingyuan Li; Hong Wei; Yuanyuan Luo; Hongdong Li (Wiley, 2023)
Abstract Neonatal bacterial meningitis is serious and accounts for high morbidity and mortality in developing countries, but the duration of antimicrobial treatment is not well established. Cerebrospinal fluid (CSF) levels are important factors for diagnosing and monitoring the occurrence and development of bacterial meningitis. In this study, we aimed to compare the clinical characteristics and outcomes of neonatal bacterial meningitis with normal CSF and abnormal CSF at discharge. We enrolled neonates with bacterial meningitis who were admitted to the neonatology department of the Children's Hospital of Chongqing Medical University between August 1, 2019 and January 1, 2021. The children's clinical data, laboratory data, and outcomes were recorded and analyzed. Fifty‐five neonates met the inclusion criteria in our study. Other than CSF protein levels, there was no significant difference in clinical symptoms, blood levels (white blood cell [WBC] count, neutrophils, platelets, C‐reactive protein, and procalcitonin), CSF WBC counts at admission and discharge, duration of antibiotics, or hospital stays between the two groups (p > 0.05). For the sequelae of bacterial meningitis, short‐ and long‐term complications also showed no statistically significant differences between the two groups. The duration of antimicrobial therapy in neonatal bacterial meningitis may depend on the clinical condition of the patient rather than the CSF levels. This study may improve the reasonable utilization of antibiotics in neonatal bacterial meningitis.